2022
DOI: 10.3390/vaccines10122083
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Asymptomatic Infection of Monkeypox Virus: A Systematic Review and Meta-Analysis

Abstract: Background: Monkeypox is a global public health concern, given the recent outbreaks in non-endemic countries where little scientific evidence exists on the disease. Specifically, there is a lack of data on asymptomatic monkeypox virus infection. This study aims to evaluate the overall prevalence of asymptomatic monkeypox virus infection. Methods: In this systematic review and meta-analysis, we performed an extensive literature search in PubMed, Scopus, Web of Science, ProQuest, EMBASE, EBSCOHost, Cochrane, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 21 publications
(115 reference statements)
0
29
0
1
Order By: Relevance
“…These cases with no sexual contacts reported contacts with apparently healthy individuals. The infectivity period for Poxviruses is typically linked to active skin lesions; however, serological studies in Africa suggest a possible role of asymptomatic/presymptomatic transmission with a pooled estimates of asymptomatic infections in a meta-analysis of 10.2% (95% CI, 2.5–17.9%) [31] . Another study, in 2022, showed that 25% of cases had known contact with confirmed Mpox cases, raising the possibility of the occurrence of asymptomatic or pauci-symptomatic transmission [32] .…”
Section: Discussionmentioning
confidence: 99%
“…These cases with no sexual contacts reported contacts with apparently healthy individuals. The infectivity period for Poxviruses is typically linked to active skin lesions; however, serological studies in Africa suggest a possible role of asymptomatic/presymptomatic transmission with a pooled estimates of asymptomatic infections in a meta-analysis of 10.2% (95% CI, 2.5–17.9%) [31] . Another study, in 2022, showed that 25% of cases had known contact with confirmed Mpox cases, raising the possibility of the occurrence of asymptomatic or pauci-symptomatic transmission [32] .…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) designated the current outbreak of Mpox disease as a Public Health Problem of International Concern on 23 July 2022 [ 4 ]. In addition, 83,487 cases were found in 110 countries by 23 December 2022 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a global emerging infectious disease threat evidenced by increasing its incidence day by day. Although the first monkeypox case was found in laboratory monkeys in Denmark in 1958, the first human case was discovered in the Democratic Republic of the Congo in 1970 2,3 . The first case of monkeypox in the USA was reported in 2003, before that the cases were only endemic in African countries such as Cameroon, Central Africa Republic, the Democratic Republic of the Congo, and Nigeria 2 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the Centers for Disease Control and Prevention, there has been an unrivalled spread of the monkeypox virus started in May 2022 which now encompasses a total of 83,539 confirmed cases of 28 December 2022, in more than 100 countries, the majority of which in formerly non‐endemic counties. So, WHO (World Health Organization) declared the contemporary epidemic of monkeypox as a Public Health Emergency of International Concern (PHEIC) 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation